Representation in an Age of Genocide - Shafer, Gregory (Radical Teacher, 2025)
Representation has become increasingly important to people of color, espcially when media outlets create monolithic images of oppressed groups. In Gaza, Palestinians remain either invisible or portrayed as terroists while Isrealis are treated to countless articles and shows on antisemtism. In the same way, other people of color, see media represent them as victims of a water crisis, never capturing the dignity and power of a people who are resilient and defy the limited images they are given. My composition class at Mott Community College critiqued the topic of representation, determined to capture their identities and contest simplistic and erroneous depictions of their status. In doing so, they became political agents of change, learning much about hegemony in a time of war and why words–like genocide–are integral to justice and equality.